Evolution, Expression Profile, Regulatory Mechanism, and Functional Verification of EBP-Like Gene in Cholesterol Biosynthetic Process in Chickens (Gallus Gallus) - Jiang, Keren; Ma, Zheng; Wang, Zhang; Li, Hong; Wang, Yanbin; Tian, Yadong; Li, Donghua; Liu, Xiaojun (Frontiers in Genetics, 2021)
The emopamil binding protein (EBP) is an important enzyme participating in the final steps of cholesterol biosynthesis in mammals. A predictive gene EBP-like, which encodes the protein with a high identity to human EBP, was found in chicken genome. No regulatory mechanisms and biological functions of EBP-like have been characterized in chickens. In the present study, the coding sequence of EBP-like was cloned, the phylogenetic trees of EBP/EBP-like were constructed and the genomic synteny of EBP-like was analyzed. The regulatory mechanism of EBP-like were explored with in vivo and in vitro experiments. The biological functions of EBP-like in liver cholesterol biosynthetic were examined by using gain- or loss-of-function strategies. The results showed that chicken EBP-like gene was originated from a common ancestral with Japanese quail EBP gene, and was relatively conservative with EBP gene among different species. The EBP-like gene was highly expressed in liver, its expression level was significantly increased in peak-laying stage, and was upregulated by estrogen. Inhibition of the EBP-like mRNA expression could restrain the expressions of EBP-like downstream genes (SC5D, DHCR24 and DHCR7) in the cholesterol synthetic pathway, therefore downregulate the liver intracellular T-CHO level. In conclusion, as substitute of EBP gene in chickens, EBP-like plays a vital role in the process of chicken liver cholesterol synthesis. This research provides a basis for revealing the molecular regulatory mechanism of cholesterol synthesis in birds, contributes insights into the improvement of the growth and development, laying performance and egg quality in poultry.